2015
DOI: 10.1017/jsc.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Cessation in Economically Disadvantaged Dominican Republic Communities: Who are the Ex-Users?

Abstract: Introduction Tobacco use and harm continue to increase in low- and middle income countries (LMICs) globally. Smoking cessation is the most effective means of reducing morbidity and mortality from tobacco use. Increasing the prevalence of ex-users is an indicator of population cessation. Aims This study provides the first examination of factors associated with ex-tobacco use status in the Dominican Republic (DR), a LMIC in the Latin America and Caribbean region. Methods Baseline surveillance was conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The recent meeting of the Working Group of the European-Latin American Respiratory Diseases Society held in Madrid showed that Latin America is making progress in smoking control [209], but that it is still necessary to increase the strictness of antismoking laws, increase taxes on cigarettes and develop alternative packaging plans. In Latin America, the results of smoking control programs have been reported in recent years [210][211][212][213][214][215][216][217][218][219][220][221][222][223][224][225][226], with excellent results obtained in Uruguay, Brazil, Chile and Panama through actions, such as the prohibition of smoking in public places, the imposition of high taxes and the inclusion of large warnings on cigarette packages, all agreed with the active participation of the leaders of governments, including, in Uruguay, the direct participation of the President of the Republic. Unfortunately, the same does not occur in other countries of the region, such as Argentina, Peru, Guatemala, Honduras and Nicaragua.…”
Section: Smokingmentioning
confidence: 99%
“…The recent meeting of the Working Group of the European-Latin American Respiratory Diseases Society held in Madrid showed that Latin America is making progress in smoking control [209], but that it is still necessary to increase the strictness of antismoking laws, increase taxes on cigarettes and develop alternative packaging plans. In Latin America, the results of smoking control programs have been reported in recent years [210][211][212][213][214][215][216][217][218][219][220][221][222][223][224][225][226], with excellent results obtained in Uruguay, Brazil, Chile and Panama through actions, such as the prohibition of smoking in public places, the imposition of high taxes and the inclusion of large warnings on cigarette packages, all agreed with the active participation of the leaders of governments, including, in Uruguay, the direct participation of the President of the Republic. Unfortunately, the same does not occur in other countries of the region, such as Argentina, Peru, Guatemala, Honduras and Nicaragua.…”
Section: Smokingmentioning
confidence: 99%
“…We continue to report findings from PDT studies elsewhere (e.g., Chin, et al in press; Dozier et al, 2006, 2009, 2014; Lando et al 2010; McIntosh, et al, 2008; Ossip-Klein, et al 2008; Ossip, et al; 2013, 2015; Prucha, et al 2015; Torres, et al 2011, 2014; Wipfli, et al 2008). The current paper will report on lessons learned from implementing this US-DR partnered research.…”
Section: Research Rationale/descriptionmentioning
confidence: 86%
“…More detail on training is provided elsewhere (Ossip-Klein, et al 2008; Ossip, et al 2015); lessons learned are presented here:…”
Section: Establishing An Infrastructure For Tobacco Cessation Researcmentioning
confidence: 99%
“…Coordination of timing of reviews is critical to ensure that all are completed prior to study initiation. In addition, some IRBs may require approval by IRBs in the other participating countries prior to providing local approval, so it is critical for investigators to be aware of such local regulations and communicate documentation of approvals to each IRB within the required time frame [ 22 , 24 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in partner Dominican Republic communities, providing written consent for participation was culturally unacceptable as it raised concerns about contractual requirements. Thus, investigators worked with all IRBs to develop an acceptable verbal consent procedure with documentation of consent provided by data collectors [ 22 , 24 , 27 , 28 ]. Understanding IRB requirements of all participating sites is critical to successful global partnerships for research [ 37 ].…”
Section: Methodsmentioning
confidence: 99%